Models of Seeing and Reading Monastic Archaeology - Brooks Hedstrom, Darlene L. (Cistercian studies quarterly, 2013)
The article focuses on sources and epistemology of Egyptian monasticism and discusses models for exploring monastic archaeology. It states that historiography of monastic archaeology begins with the work of early archaeologists and surveyors who were primarily concerned with evidence from pharaonic Egypt. It further mentions that the adoption of theoretical models for classifying sites and reading archaeological material will provide a more comprehensive portrait of Egyptian monasticism.